Factors Affecting Intention to Recommend Halal Cosmetic Products (Case Study in South Tangerang City) - Devany Arfilia Susanti; Edy Yusuf Agung Gunanto (Jurnal Ekonomi Syariah Teori dan Terapan, 2022)
ABSTRAK Sektor kosmetik halal saat ini dianggap sebagai sektor dengan potensi tertinggi secara global. Berkembangnya tren penggunaan kosmetik halal dipengaruhi oleh tren hijrah dan gaya hidup umat Muslim yang sadar dengan urgensi penggunaan produk halal. Ketersediaan produk kosmetik halal yang beragam di pasaran mendorong konsumen lebih diskriminatif dalam pemilihan merek kosmetiknya. Perusahaan perlu merumuskan strategi pemasaran yang tepat agar produknya dapat bertahan dan bersaing dengan kompetitor, salah satunya melalui rekomendasi atas suatu produk tertentu. Penelitian ini bertujuan untuk menganalisis faktor yang mempengaruhi intensi konsumen untuk merekomendasikan produk kosmetik halal. Metode yang digunakan dalam penelitian yaitu Structural Equation Modelling (SEM) dengan alat analisis SmartPLS 3. Data primer diperoleh melalui kuesioner dengan 180 sampel masyarakat di Kota Tangerang Selatan. Hasil penelitian mengungkapkan bahwa customer satisfaction, product quality, dan customer experience berpengaruh secara positif dan signifikan terhadap intention to recommend produk kosmetik halal, sedangkan trust tidak berpengaruh secara signifikan terhadap intention to recommend produk kosmetik halal. Kata kunci: Kosmetik halal, customer satisfaction, trust, product quality, customer experience, intention to recommend.   ABSTRACT The halal cosmetics sector is currently considered the sector with the highest potential in the world. The growing trend of using halal cosmetics is influenced by the migration trend and lifestyle of Muslims who are aware of the importance of using halal products. The presence of various halal cosmetic products on the market encourages consumers to be more selective in their choice of cosmetic brands. Companies need to formulate the right marketing strategy in order for their products to survive and compete with competitors, one of which is product-specific recommendations. This study aims to analyze the factors that influence consumers' intentions to recommend halal beauty products. This study used Structural Equation Modeling (SEM) with the SmartPLS 3 analysis tool. Primary data was obtained from a survey of 180 samples of people in the city of South Tangerang. The results of the study show that customer satisfaction, product quality, and customer experience have a positive and significant impact on the intention to recommend halal beauty products, while trust does not have a significant effect on the intention to recommend halal beauty products. Keywords: Halal cosmetics, customer satisfaction, trust, product quality, customer experience, intention to recommend.   DAFTAR PUSTAKA Abu Bakar, E., Rosslee, N. N., Mastura, A., Ariff, M., Othman, M., & Hashim, P. (2017). Consumers’ trust and values towards halal cosmetics and personal care products. Malaysian Journal of Consumer and Family Economics. Adriyati, R., & Indriani, F. (2017). Pengaruh electronic word of mouth terhadap citra merek dan minat beli pada produk kosmetik wardah. Diponegoro Journal of Management, 6(4), 1–14. Ahmadi, A. (2019). Thai Airways: Key influencing factors on customers’ word of mouth. International Journal of Quality and Reliability Management, 36(1), 40–57. https://doi.org/10.1108/IJQRM-02-2018-0024 Ajzen, I. (1988). Attitudes, personality and behavior. Open University Press. Al-Ansi, A., Olya, H. G. T., & Han, H. (2019). Effect of general risk on trust, satisfaction, and recommendation intention for halal food. International Journal of Hospitality Management, 83, 210–219. https://doi.org/10.1016/j.ijhm.2018.10.017 Ali, F., Kim, W. G., Li, J., & Jeon, H. M. (2018). Make it delightful: Customers’ experience, satisfaction and loyalty in Malaysian theme parks. Journal of Destination Marketing and Management, 7, 1–11. https://doi.org/10.1016/j.jdmm.2016.05.003 Ali, F., Rasoolimanesh, S. M., Sarstedt, M., Ringle, C. M., & Ryu, K. (2018). An assessment of the use of partial least squares structural equation modeling (PLS-SEM) in hospitality research. International Journal of Contemporary Hospitality Management, 30(1), 514–538. Annabi, C. A., & Ibidapo-Obe, O. O. (2017). Halal certification organizations in the United Kingdom: An exploration of halal cosmetic certification. Journal of Islamic Marketing, 8(1), 107–126. https://doi.org/10.1108/JIMA-06-2015-0045 Augusty Ferdinand. (2006). Metode penelitian manajemen: Pedoman penelitian untuk penulisan skripsi, tesis, dan disertasi ilmu manajemen. Semarang: Badan Penerbit Universitas Diponegoro. Bennet, R., & Rundle-Thiele, S. (2004). Customer satisfaction should not be the only goal. Journal of Services Marketing, 18(7), 514–523. BPJPH. (2020). Bahan halal dalam sertifikasi halal. Retrieved from http://halal.go.id/beritalengkap/236 Chang, H. H., Jeng, D. J. F., & Hamid, M. R. A. (2013). Conceptualising consumers’ word-of-mouth behaviour intention: Evidence from a university education services in Malaysia. Service Business, 7(1), 17–35. https://doi.org/10.1007/s11628-012-0142-1 Chang, S. E., Shen, W. C., & Yeh, C. H. (2017). A comparative study of user intention to recommend content on mobile social networks. Multimedia Tools and Applications, 76(4), 5399–5417. https://doi.org/10.1007/s11042-016-3966-1 Chen, J., & Shen, X. L. (2015). Consumers’ decisions in social commerce context: An empirical investigation. Decision Support Systems, 79, 55–64. https://doi.org/10.1016/j.dss.2015.07.012 Deshwal, P. (2016). Customer experience quality and demographic variables (age, gender, education level, and family income) in retail stores. International Journal of Retail and Distribution Management, 44(9), 940–955. https://doi.org/10.1108/IJRDM-03-2016-0031 Dinar Standard. (2020). State of the global Islamic economy report thriving in uncertainty. Retrieved from https://www.salaamgateway.com/specialcoverage/SGIE20-21 Fishbein, M., Ajzen, I., & Flanders, A. N. (1975). Belief, attitude, intention, and behavior: An introduction to theory and research (Icek Ajzen (ed.); Vol. 2089). Addison-Welsey Publishing Company. Ghozali, I. (2014). Partial least squares, konsep, teknik, dan aplikasi menggunakan program SmartPLS 3.2.9 untuk peneliti. Semarang: Badan Penerbit Universitas Diponegoro. Hashim, A. J. bt C. M., & Musa, R. (2014). Factors influencing attitude towards halal cosmetic among young adult urban Muslim women: A focus group analysis. Procedia - Social and Behavioral Sciences, 130, 129–134. https://doi.org/10.1016/j.sbspro.2014.04.016 Hussein, A. S., Hapsari, R. D. V., & Yulianti, I. (2018). Experience quality and hotel boutique customer loyalty: Mediating role of hotel image and perceived value. Journal of Quality Assurance in Hospitality and Tourism, 19(4), 442–459. https://doi.org/10.1080/1528008X.2018.1429981 Iglesias, O., Singh, J. J., & Batista-Foguet, J. M. (2011). The role of brand experience and affective commitment in determining brand loyalty. Journal of Brand Management, 18(8), 570–582. https://doi.org/10.1057/bm.2010.58 Ishak, S., Che Omar, A. R., Khalid, K., Intan, I. S., & Hussain, M. Y. (2020). Cosmetics purchase behavior of educated millennial Muslim females. Journal of Islamic Marketing, 11(5), 1055–1071. https://doi.org/10.1108/JIMA-01-2019-0014 Izogo, E. E. (2016). Structural equation test of relationship quality: Repurchase intention – willingness to recommend framework in retail banking. International Journal of Emerging Markets, 11(3), 374–394. https://doi.org/10.1108/IJOEM-07-2015-0130 Jani, D., & Han, H. (2014). Personality, satisfaction, image, ambience, and loyalty: Testing their relationships in the hotel industry. International Journal of Hospitality Management, 37, 11–20. Jaswir, I., Rahayu, E. A., Yuliana, N. D., & Roswiem, A. P. (2020). Daftar referensi bahan-bahan yang memiliki titik kritis halal dan substitusi bahan non-halal (1st ed.). Jakarta: Komite Nasional Ekonomi dan Keuangan Syariah (KNEKS). Jung, H., & Soo, M. (2012). The effect of brand experience on brand relationship quality. In Academy of Marketing Studies Journal, 16(1), 87-98. Kaur, K., Osman, S., & Maziha, S. (2014). Predicting working women purchasing behaviour of Malaysian halal cosmetic products by using theory of planned behaviour. International Academic Research Journal of Business and Management. Kemenperin. (2021). Wujudkan masterplan ekonomi syariah, kemenperin pacu kawasan industri halal. Retrieved from https://kemenperin.go.id/artikel/22818/Wujudkan-Masterplan-Ekonomi-Syariah,-Kemenperin-Pacu-Kawasan-Industri-Halal Khan, N., Sarwar, A., & Tan, B. C. (2021). Determinants of purchase intention of halal cosmetic products among Generation Y consumers. Journal of Islamic Marketing, 12(8), 1461–1476. https://doi.org/10.1108/JIMA-11-2019-0248 Kim, H. S., & Choi, B. (2016). The effects of three customer-to-customer interaction quality types on customer experience quality and citizenship behavior in mass service settings. Journal of Services Marketing, 30(4), 384–397. https://doi.org/10.1108/JSM-06-2014-0194 Kotler, P., & Armstrong, G. (2018). Principles of marketing. London: Pearson Education Limited. Kotler, P., & Keller, K. L. (2012). Marketing management. London: Pearson Education. Kraeuter, S. G. (2002). The role of consumers’ trust in online-shopping. Journal of Business Ethics, 39(1), 43–50. http://dx.doi.org/10.1023/A:1016323815802 LPPOM MUI. (2021). LPPOM: Wajib sertifikasi halal juga berlaku untuk produk kosmetik. Retrieved from https://mui.or.id/berita/32650/lppom-wajib-sertifikasi-halal-juga-berlaku-untuk-produk-kosmetik/ Marques, C., Vinhas da Silva, R., & Antova, S. (2021). Image, satisfaction, destination and product post-visit behaviours: How do they relate in emerging destinations? Tourism Management, 85. https://doi.org/10.1016/j.tourman.2021.104293 Meilatinova, N. (2021). Social commerce: Factors affecting customer repurchase and word-of-mouth intentions. International Journal of Information Management, 57. https://doi.org/10.1016/j.ijinfomgt.2020.102300 Morgan, R. M., & Hunt, S. D. (1994). The commitment-trust theory of relationship marketing. Journal of Marketing, 58(3), 20–38. https://doi.org/10.2307/1252308 Oliveira, T., Tomar, S., & Tam, C. (2020). Evaluating collaborative consumption platforms from a consumer perspective. Journal of Cleaner Production, 273. https://doi.org/10.1016/j.jclepro.2020.123018 Oliver, R. L. (1980). A cognitive model of the antecedents and consequences of satisfaction decisions. Journal of Marketing Research, 17(4), 460-469. https://doi.org/10.2307/3150499 Özmen, A., & Ögel, İ. Y. (2020). The interaction between customer experience, satisfaction and positive word of mouth: A study on city marketing in Afyonkarahisar. Contemporary Issues in Business Economics and Finance (Contemporary Studies in Economic and Financial Analysis, 104, 105–121). https://doi.org/10.1108/s1569-375920200000104007 Robustin, T. P., Fauziah, A., Widya, S., & Lumajang, G. (2018). Pengaruh kualitas produk dan word of mouth terhadap keputusan pembelian kosmetik wardah pada masyarakat di kota Jember. Prosiding Seminar Nasional Manajemen dan Bisnis III, 94–101. Safa, N. S., & Von Solms, R. (2016). Customers repurchase intention formation in e-commerce. SA Journal of Information Management, 18(1). https://doi.org/10.4102/sajim.v18i1.712 Schmitt, B. (1999). Experiential marketing. Journal of Marketing Management, 15(1–3), 53–67. https://doi.org/10.1362/026725799784870496 Sugibayashi, K., Yusuf, E., Todo, H., Dahlizar, S., Sakdiset, P., Arce, F. J., & See, G. L. (2019). Halal cosmetics: A review on ingredients, production, and testing methods. Cosmetics, 6(3), 1–17. https://doi.org/10.3390/cosmetics6030037 Suhartanto, D., Dean, D., Sarah, I. S., Hapsari, R., Amalia, F. A., & Suhaeni, T. (2021). Does religiosity matter for customer loyalty? Evidence from halal cosmetics. Journal of Islamic Marketing, 12(8), 1521–1534. https://doi.org/10.1108/JIMA-03-2020-0069 Tenenhaus, M., Vinzi, V. E., Chatelin, Y. M., & Lauro, C. (2005). PLS path modeling. Computational Statistics and Data Analysis, 48(1), 159–205. https://doi.org/10.1016/j.csda.2004.03.005 Tjiptono, F., & Chandra, G. (2012). Pemasaran Strategik. Yogyakarta: Andi. Van Wangenheim, F., & Bayón, T. (2007). The chain from customer satisfaction via word-of-mouth referrals to new customer acquisition. Journal of the Academy of Marketing Science, 35(2), 233–249. https://doi.org/10.1007/s11747-007-0037-1 Wangenheim, F. V. (2005). Postswitching negative word of mouth. Journal of Service Research, 8(1), 67–78. https://doi.org/10.1177/1094670505276684 Yuliana, A., & Wahyudi, L. (2021). The relationship between trust and intention to recommend: The role of content quality, website design and enjoyment. Journal of Business and Management Studies, 3(2), 241-248. https://doi.org/10.32996/jbms